Characterization and antigenicity of the promising vaccine candidate Plasmodium vivax 34 kDa rhoptry antigen (Pv34) (2009)
This study describes the identification of the Plasmodium vivax rhoptry antigen Pv34 whose sequence was obtained based on homology comparison with the Plasmodium falciparum Pf34. The pv34 gene product was characterized by molecular biology and immunological techniques. Additionally, association of Pv34 to detergent-resistant microdomains (DRMs), expression in late blood-stage parasites and recognition of recombinant Pv34 (rPv34) by sera from P. vivax-infected Aotus monkeys and patients was assessed. Lymphoproliferation and cytokine secretion was also evaluated in individuals living in malaria endemic areas. Altogether, the data support carrying out further studies to assess the immunogenicity and protection-inducing ability of rPv34 as component of a multi-antigenic, multi-stage vaccine against vivax malaria. © 2009 Elsevier Ltd. All rights reserved.